The third Sector’s role and influence in addressing local environmental issues in Perth, Western Australia. - Dhakal, Subas P. (Australian and New Zealand Third Sector Research Inc., 2011)
The position of the third sector in fulfilling collective environmental aspirations has been strengthening in Australia, at least partially due to the growing number of Environmental Community Organisations (ECOs). ECOs play an important role in the ongoing stewardship of the natural environment; their duties range from managing local nature reserves to mounting public campaigns in order to curtail further environmental degradation. However, apart from being labelled as an ‘interest organisations’, ECOs in general have slipped under the radar of third sector research in Australia.